E11 Association Between Brain Volume and White Matter Microstructure in Healthy Controls. (17th September 2014) - Crawford, HE; Gregory, S; Hobbs, NZ; Johnson, H; Cole, JH; Rees, EM; Malone, IB; Sprengelmeyer, R; Durr, A; Leavitt, BR; Roos, RAC; Langbehn, DR; et al.
Abstract : Background: Macrostructural and microstructural neuroimaging measures are potential biomarkers in Huntington's disease (HD). Macrostructural measures are generally derived from structural T1-weighted magnetic resonance imaging (MRI), while microstructure can be measured using diffusion tensor imaging (DTI), which indexes the properties of water molecules within white matter (WM) tissue. HD is associated with WM volume and integrity loss but how these two measures interact is not fully understood. Aims: To investigate the relationship between diffusion metrics and brain volume in healthy controls. Methods: 3T MRI and DTI data from 51 control subjects taken from the TRACK-HD and PADDINGTON studies were analysed. Regression analysis and Tract Based Spatial Statistics (TBSS) were used to assess the associations between whole brain diffusion metrics: fractional anisotropy; mean diffusivity; axial diffusivity and radial diffusivity, and volumetric measures: whole brain volume; WM and grey matter (GM) volumes (all adjusted for total intracranial volume). Results: Regression analysis revealed a significant relationship between all diffusion metrics and both whole brain and WM volumes. No significant relationship was found between GM and FA. Preliminary TBSS results suggest a significant positive association between whole brain volume and FA in several regions, including the cingulate gyrus, pre- and post central gyri and the putamen. Conclusions: We demonstrated an association between whole brain and WM volume and diffusion-based measures of tissue integrity; this relationship is present in the absence of any disease-related changes. These results may aid our understanding of the underlying pathology and heterogeneity in HD and have implications for biomarker development in the condition.